2011
DOI: 10.1007/s12070-011-0387-3
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Complications and Morbidity Profile in Cochlear Implantation: The MERF Experience

Abstract: Cochlear implantation (CI) has been established worldwide as the surgical treatment for individuals with bilateral severe to profound hearing loss. This is a safe and standard procedure in the hands of experienced implant surgeons. Complications due to surgery are minimal and are often encountered in cases with congenital anomalies of the temporal bone and inner ear. Complications in CI are related to malfunctioning of the device or the process of wound healing. In most cochlear implant centers, as the surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…The most common complications of cochlear implantation are: flap necrosis, infection, rupture and resultant device explantation ( Trinidade et al., 2008 ). In our study, the rate of complications related to flap around implants was 3.7%, while rates of complications reported in the literature range from 0.06% to 10% ( Raghunandhan et al., 2014 , Ajallouyean et al., 2011 , Cunningham et al., 2004 , Rubienstein et al., 1999 , Hopfenspirger et al., 2007 , Cohen and Hoffman, 1991 , Kempf et al., 1999 ).…”
Section: Discussionmentioning
confidence: 41%
“…The most common complications of cochlear implantation are: flap necrosis, infection, rupture and resultant device explantation ( Trinidade et al., 2008 ). In our study, the rate of complications related to flap around implants was 3.7%, while rates of complications reported in the literature range from 0.06% to 10% ( Raghunandhan et al., 2014 , Ajallouyean et al., 2011 , Cunningham et al., 2004 , Rubienstein et al., 1999 , Hopfenspirger et al., 2007 , Cohen and Hoffman, 1991 , Kempf et al., 1999 ).…”
Section: Discussionmentioning
confidence: 41%
“…This study also reveals that electrode fixation was not a matter of concern in the techniques analyzed, given that the rate of electrode extrusion in over 1000 patients was 0.79% in SMA and 1.88% for the transcanal approach. Junior et al 8 reported one case (0.4%) of electrode exclusion out of 250 cases that underwent CI by the PA approach, and Raghunandhan et al 30 reported another single case (0.3%), out of 300 cases that underwent CI by the PT approach.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative complications are wound infection, skin necrosis, facial paralysis, seroma, vertigo, meningitis and tinnitus. One of the potentially critical complications of CI is meningitis and precautions should be taken in all cases, especially if a cerebrospinal gusher occurs after opening the cochlea 7. Late postoperative complications include failure of the device, facial nerve twitching on stimulation and chronic ear infection with or without cholesteatoma.…”
mentioning
confidence: 99%